Scanning Electron Microscopic Evaluation of Smear Layer Removal Using Isolated or Interweaving EDTA with Sodium Hypochlorite - da Silva Beraldo, Ângelo José; Silva, Rogério Vieira; da Gama Antunes, Alberto Nogueira; Silveira, Frank Ferreira; Nunes, Eduardo (Iranian Endodontic Journal, 2016)
Introduction: The aim of this study was to verify the effect of alternating 2.5% sodium hypochlorite (NaOCl) and 17% ethylenediaminetetraacetic acid (EDTA) on the smear layer removal from root canal surfaces. Methods and Materials: A total of 15 single-rooted human teeth, instrumented with ProTaper files, were randomly distributed in 3 groups. In group 1 (n=7) the canals were irrigated with 1 mL of 2.5% NaOCl between files and final irrigation was done with 1 mL of 2,5% NaOCl, followe by 1 mL of 17% EDTA, for a perio of 15 sec with new irrigtion of 1 mL of 2,5% NaOCl at each change of files. In group 3 (control group) (n=1), saline solution was used. All samples were cleaved into two sections, metalized and analyzed under scanning electron microscopy (SEM). The presence or absence of smear layer in the cervical, middle and apical thirds, with scores varying from 1 to 3, respectively were evaluated. The data were submitted to nonparametric Mann-Whitney U test. The level of significance was set at 0.05. Results: It was observed that there was a greater discrepancy between groups with respect to the apical third. In the other areas there was a greater similarity between the scores attributed to the groups. There was a statistically significant difference between the groups only in the apical third, when group 1 presented the higher median (P<0.05). Conclusion: The alternating use of EDTA during instrumentation with NaOCl was the most effective irrigation method to remove the apical smear layer. Both forms of irrigation were effective on removal of the smear layer in the coronal and middle thirds of the canals. Keywords: Root Canal Irrigants; Scanning Electron Microscopy; Smear Layer